Ultrasound-guided microwave ablation in the treatment of early-stage tongue cancer - Yang, Jianquan; Guo, Wen; Huang, Rong; Xu, Zhengmin; Zhou, Chunyang; Lu, Man (Frontiers in Oncology, 2022)
Here, we report a case of microwave ablation (MWA) for early-stage tongue cancer (ESTC) due to the inability to perform general surgery. The ablation was successfully performed under the lingual nerve block. The patient was followed one year, she recovered well with no dysphagia, unclear articulation symptoms, and the cosmetic effect was excellent. Moreover, complete remission of tumor lesions was determined by ultrasound contrast agent and puncture biopsy. To our knowledge, this is the first case to using MWA for the treatment of ESTC. Ultrasound-guided MWA may be used for ESTC which can completely ablate tumor and retains the function of the tongue, further improving the quality life of patient. However, it is only a case report, and needs more research to verify MWA in ESTC.